Brand Identity Dominance in Political Candidate Image Construction: Dominasi Identitas Merek dalam Konstruksi Citra Kandidat Politik - Fawwaz Hanif Basyaeb; M Andi Fikri (Academia Open, 2025)
General Background: Social media platforms function as strategic channels for political communication and candidate image construction in electoral campaigns. Specific Background: TikTok is increasingly used by political candidates to deliver symbolic messages and engage voters during regional elections. Knowledge Gap: Limited research examines local political candidate branding strategies on TikTok using phenomenological approaches. Aims: This study analyzes the personal branding of Mas Rusdi as a Pasuruan Regent candidate through the TikTok account @masrusdi.official using personal branding theory. Results: Using a qualitative phenomenological method, findings indicate that Mas Rusdi presents an image as a progressive young leader through consistent brand positioning, displays religious political jargon as brand identity, demonstrates concern for public issues including regional football development as brand personality, and applies brand communication through TikTok trends using fast-paced visuals and light narrative storytelling. Informants perceive brand identity as the dominant component shaping public perception during the 2024 regional election campaign. Novelty: This study provides a concise phenomenological description of local political branding practices through TikTok content. Implications: The findings contribute to political communication studies by providing insights into culturally contextualized digital campaign strategies in regional elections. Highlights: Progressive Leadership Representation Consistently Appeared Through Youth-Oriented Positioning. Religious Slogan Usage Strengthened Symbolic Recognition Among Followers. Trend-Based Audiovisual Storytelling Increased Audience Engagement Patterns. Keywords: Political Communication, Digital Campaign Strategy, Regional Election Branding, Phenomenological Analysis, Candidate Image Construction